2015
DOI: 10.1155/2016/6705621
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Regulates Mitochondrial Biogenesis and Fission/Fusion to Attenuate Rotenone‐Induced Neurotoxicity

Abstract: It has been confirmed that mitochondrial impairment may underlie both sporadic and familial Parkinson's disease (PD). Mitochondrial fission/fusion and biogenesis are key processes in regulating mitochondrial homeostasis. Therefore, we explored whether the protective effect of resveratrol in rotenone-induced neurotoxicity was associated with mitochondrial fission/fusion and biogenesis. The results showed that resveratrol could not only promote mitochondrial mass and DNA copy number but also improve mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 33 publications
7
56
0
Order By: Relevance
“…In addition, this study showed that resveratrol treatments increase both mitochondrial mass and mtDNA contents during osteogenic differentiation in PO-MSCs. These findings indicate that resveratrol can up-regulate mitochondrial biogenesis during osteogenic differentiation of PO-MSCs and are consistent with other reports regarding mitochondrial biogenesis by resveratrol in various cell types (26,(38)(39)(40)(41)(42). Moreover, the up-regulation of mitochondrial biogenesis by resveratrol in PO-MSCs is in line with the notion that metabolic shift from glycolysis to mitochondrial OXPHOS occurs during stem cell differentiation (16,17,(43)(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this study showed that resveratrol treatments increase both mitochondrial mass and mtDNA contents during osteogenic differentiation in PO-MSCs. These findings indicate that resveratrol can up-regulate mitochondrial biogenesis during osteogenic differentiation of PO-MSCs and are consistent with other reports regarding mitochondrial biogenesis by resveratrol in various cell types (26,(38)(39)(40)(41)(42). Moreover, the up-regulation of mitochondrial biogenesis by resveratrol in PO-MSCs is in line with the notion that metabolic shift from glycolysis to mitochondrial OXPHOS occurs during stem cell differentiation (16,17,(43)(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 92%
“…The cells showing 70% fragmented or intermediate mitochondria were classified as fragmented cells [42]; their number increased significantly upon infliction of oxidative treatment and, not surprisingly, Cr preloading prevented this effect (Figure 1(d)). …”
Section: Resultsmentioning
confidence: 99%
“…Type I (slow-twitch) muscle fibres are rich in the mitochondria (3,32) . It has been reported that some nutrients (such as leucine and resveratrol) can regulate type I (slowtwitch) muscle fibres expression by improving the mitochondrial biogenesis and function (29,30,33) . In the present study, our data found that dietary supplementation of 1•0 % Arg significantly increased the PGC-1α, Sirt1 and Cytc protein expressions, the PGC-1α, NRF1, TFB1M, Cytc and ATP5G mRNA expressions and the mtDNA content, suggesting that Arg plays an important role in regulating mitochondrial biogenesis and function.…”
Section: Discussionmentioning
confidence: 99%